Novas tecnologias e a transformação da advocacia: entre a tradição e a empresarialidade - Laurence Duarte Araújo Pereira (2022)
In recent decades, advocacy in Brazil has undergone transformations that have completely changed the way it is exercised. Research shows that, with the liberalization of the Brazilian economy, especially in the 1990s, law firms changed from personalized and artisanal structures to structures similar to companies. In recent years, this movement has intensified and accelerated, mainly due to the influence of technological innovations in the field of law, in addition to the emergence of lawtechs and legaltechs, technology companies that operate in the legal market. The issue of the future of law, in this scenario, has become of relevant discussions between regulators, academics, law firms, businessmen and even the judiciary, which has already faced causes in which the legal nature of law firms, wheter business or not, has been under discussion. The present research aims to study the transformation of advocacy into corporate activity, starting, first, with a study on the origins of advocacy in Brazil and its regulation, also going through the study of the legal discipline of business activity in Brazilian legislation. Then, we study the market movement of the last decades and the way law firms in Brazil behave today, in order to, in sequence, study the role of technology in this transformation. The research was carried out through a critical view of reality, in order to observe, in practice, the nature of law firms in Brazil, despite the way they are regulated. Finally, through an exploratory methodology, we seek to present, based on examples of countries in wich law firms activities were flexibilizated, the known and expected challenges for the future of law firms, as well as legislative guidelines for an adequacy of Brazilian law to the new reality of law in Brazil, including with regard to new technologies. Finally, we conclude that, although the legal regime of advocacy in Brazil regulates the activity as an intellectual, personalist and artisanal activity, in practice, a good part of the law firms in Brazil and, in some cases, even autonomous lawyers, carry out corporate activities. There is, therefore, a legislative inadequacy on the subject. By exploring the challenges of the future of advocacy and the legislative frameworks presented in this research, we intend to contribute to further research on the subject, and also to contribute to debates for an adequate legislation to this new reality.